Isolated complete ulnar collateral ligament tear of the elbow in a gymnast: does it need surgery? - Dubin, J. M.; Rojas, J. L.; Borade, A. U.; Familiari, F.; McFarland, E. G. (The Physician and Sportsmedicine, 2019)
Ulnar collateral ligament (UCL) tears can occur from trauma or chronic overuse, and the treatment depends on the type of sport the patient plays and the severity of symptoms. Overuse UCL injuries are most commonly due to micro-trauma in overhead athletes such as baseball players, softball players, and tennis players. Acute complete UCL tears in athletes due to trauma are less common but generally operative treatment is recommended. In gymnastics, elbow dislocations are more common than isolated UCL injuries, and there is sparse literature on the success of non-operative treatment of isolated UCL injuries in this group of athletes. In this case report, we report a high-level competitive gymnast with an UCL tear and a partial tear of the forearm flexor mass, which was confirmed by a thorough careful physical examination and magnetic resonance imaging. The patient was treated non-operatively and successfully returned to gymnastics without symptoms. This case supports the suggestion that UCL tears of the elbow can be treated successfully in some gymnasts without surgery, and that treatment should be individualized in this group of athletes.